2016
DOI: 10.1371/journal.pone.0152312
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinicopathological Features and Treatments between Young (≤40 Years) and Older (>40 Years) Female Breast Cancer Patients in West China: A Retrospective, Epidemiological, Multicenter, Case Only Study

Abstract: The incidence of young cases of breast cancer is higher in China compared to the western world. We aimed to explore differences in risk factors, clinicopathological features and treatment modes of young female breast cancer compared to older patients in West China. We collected clinical information from 12,209 female breast cancer patients in West China, including risk factors, clinicopathological features and treatment modes, from January 2010 to December 2012. Chi-square tests and the multivariate logistic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
47
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(62 citation statements)
references
References 39 publications
13
47
0
2
Order By: Relevance
“…We obtained similar results. Those results are similar to that in another article from the same database 32. Additionally, higher proportion of (ER+/PR+) in premenopausal patients and higher proportion of (ER−/PR−) in postmenopausal patients suggested that the distribution of hormone receptors in western Chinese women is different from that in foreign countries.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…We obtained similar results. Those results are similar to that in another article from the same database 32. Additionally, higher proportion of (ER+/PR+) in premenopausal patients and higher proportion of (ER−/PR−) in postmenopausal patients suggested that the distribution of hormone receptors in western Chinese women is different from that in foreign countries.…”
Section: Discussionsupporting
confidence: 89%
“…Breast cancer is age‐dependent, and it is widely accepted that young women tend to present with a greater tumor size that is more advanced and with poorer prognostic characteristics 31, 32. We found that premenopausal women presented with a greater tumor size (more than 2 cm) than postmenopausal women in our study.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…The proportion of patients who underwent surgery in the present study was 86.84%, lower than in the previous study. This difference is primarily because the previous study only included one or two hospitals in each city, while the patients in our study may have undergone surgery in one hospital but were treated in several others . The influence of age on the choice of treatment modes has been discussed by previous studies.…”
Section: Discussionmentioning
confidence: 95%
“…Hanrahan et al reported the median age at diagnosis of early‐stage BC to be 65 years among 51 246 patients in the SEER database, compared with a median age of 49 years in a study of 868 Chinese women with stage I‐III BC . Second, the percentage of patients with BC who are younger than 40 years old in Western countries is only 5% to 9.6%, compared with approximately 20% in Asian countries …”
Section: Introductionmentioning
confidence: 99%